Media Sosial sebagai Sarana Komunikasi Strategis dalam Pengembangan dan Promosi Ekowisata (Studi Kasus UKM Ekowisata di Pengalengan, Jawa Barat) - Runtiko, Agus Ganjar; Rosyadi, Slamet; Yamin, Muhammad; Syarif Hidayat, Amri (Sodality: Jurnal Sosiologi Pedesaan, 2023)
This research explores the role of social media as a strategic communication tool in developing and promoting ecotourism enterprise. The research was conducted by studying five social media used by Ecoethno Leadcampsite, an ecoturism site located in Pengalengan, West Java runned by a Small and Medium Enterprise (SME). This study assesses how social media is used to strengthen the visibility of these destinations, facilitate engagement with tourists, and promote sustainable tourism practices. The research findings show that not all social media are used effectively, and they tend to highlight certain aspects of strategic communication, including tourism activities, resource utilization, and environmental orientation. Strategic communication aspects of travel expenses, timetables, and customer care are relatively not covered in the marketing communications messages. Insights from this research have implications for tourism stakeholders, policymakers, and society in general, demonstrating the need for a paradigm shift towards integrated use of digital technology to promote and build sustainable ecotourism.